2006
DOI: 10.1073/pnas.0607050103
|View full text |Cite
|
Sign up to set email alerts
|

The GLD-2 poly(A) polymerase activates gld-1 mRNA in the Caenorhabditis elegans germ line

Abstract: mRNA regulation is crucial for many aspects of metazoan development and physiology, including regulation of stem cells and synaptic plasticity. In the nematode germ line, RNA regulators control stem cell maintenance, the sperm͞oocyte decision, and progression through meiosis. Of particular importance to this work are three GLD (germ-line development) regulatory proteins, each of which promotes entry into the meiotic cell cycle: GLD-1 is a STAR͞Quaking translational repressor, GLD-2 is a cytoplasmic poly(A) pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
116
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(128 citation statements)
references
References 28 publications
(30 reference statements)
5
116
0
Order By: Relevance
“…A polyadenylationdependent mechanism has been previously established during the mitosis-meiosis decision in the Caenorhabditis elegans germ line. In this organism, a regulatory cytoplasmic polyadenylation complex stimulates the expression of meiotic genes (46,47). Whereas this cytoplasmic pathway represents a positive regulatory step that reinforces commitment to the meiotic cycle in C. elegans, the Pab2-dependent mechanism described in this study is nuclear and represents a negative regulatory step to prevent untimely expression of meiotic genes.…”
Section: Discussionmentioning
confidence: 94%
“…A polyadenylationdependent mechanism has been previously established during the mitosis-meiosis decision in the Caenorhabditis elegans germ line. In this organism, a regulatory cytoplasmic polyadenylation complex stimulates the expression of meiotic genes (46,47). Whereas this cytoplasmic pathway represents a positive regulatory step that reinforces commitment to the meiotic cycle in C. elegans, the Pab2-dependent mechanism described in this study is nuclear and represents a negative regulatory step to prevent untimely expression of meiotic genes.…”
Section: Discussionmentioning
confidence: 94%
“…It is known that GLP-1/Notch signaling is both necessary and sufficient for germline proliferation at the expense of differentiation, while Gld-1 inhibits germline mitosis and negative feedback regulates GLP-1/Notch signaling [53][54][55]. In the mitotic region, GLP-1 proteins are present close to where DTC is [56,57], while GLD-1 is present close to the transition zone [24,26], making gld-1 a top candidate gene responsible for the loss of germ cells in gk262. Indeed, our experiments indicate that mir-35 directly targets gld-1 and a higher than normal level of GLD-1 inhibits germ cell mitosis (Figures 4 and 5).…”
Section: Discussionmentioning
confidence: 99%
“…In the gonad, GLP-1 (abnormal Germ Line Proliferation)/Notch signaling is essential to promote germ line divisions in distal mitotic region [19][20][21][22]. GLD (defective in Germ Line Development) family plays a key role in determining meiosis entry and indirectly regulates mitotic proliferation of the germline [23][24][25][26][27]. We found that mir-35 may down-regulate gld-1 to ensure a normal germline proliferation in distal the mir-35 mutant gk262, less intestinal nuclei were observed than the wide type, at 3-fold and L3/L4 stages, respectively (Table 1, P < 0.001, Student t-test).…”
Section: Lacking Mir-35 Causes Decrease Of Intestinal Nuclei Numbersmentioning
confidence: 99%
“…Many of the germline-expressed genes were shown to function in meiotic processes, such as chromosome pairing, recombination, and segregation (e.g., zim-1, zim-2, zim-3, him-3, him-8). Additional known genes identified are gld-2, which encodes a translational activator (Suh et al 2006), and nos-3, which encodes a member of the Nanos family of RNA-binding proteins (Hansen et al 2004)-both are key regulators of entry into meiosis (Kimble and Crittenden 2007).…”
Section: Discussionmentioning
confidence: 99%